Towards a Biomanufactory on Mars - Berliner, Aaron J.; Hilzinger, Jacob M.; Abel, Anthony J.; McNulty, Matthew J.; Makrygiorgos, George; Averesch, Nils J. H.; Sen Gupta, Soumyajit; Benvenuti, Alexander; Caddell, Daniel F.; Cestellos-Blanco, Stefano; Doloman, Anna; Friedline, Skyler; et al. (Frontiers in Astronomy and Space Sciences, 2021)
A crewed mission to and from Mars may include an exciting array of enabling biotechnologies that leverage inherent mass, power, and volume advantages over traditional abiotic approaches. In this perspective, we articulate the scientific and engineering goals and constraints, along with example systems, that guide the design of a surface biomanufactory. Extending past arguments for exploiting stand-alone elements of biology, we argue for an integrated biomanufacturing plant replete with modules for microbial in situ resource utilization, production, and recycling of food, pharmaceuticals, and biomaterials required for sustaining future intrepid astronauts. We also discuss aspirational technology trends in each of these target areas in the context of human and robotic exploration missions.